Α1-Antitrypsin deficiency 3: Clinical manifestations and natural history. Issue 5 (28th April 2004) - Needham, M; Stockley, R A
Abstract : A review of the clinical manifestations of α1 -antitrypsin (AAT) deficiency, including lung disease and liver disease, and risk factors affecting the rate of decline in lung function in AAT deficient patients.